Implication of a Central Cysteine Residue and the HHCC Domain of Moloney Murine Leukemia Virus Integrase Protein in Functional Multimerization - Donzella, George A. (American Society for Microbiology, 1998)
Moloney murine leukemia virus (M-MuLV) IN-IN protein interactions important for catalysis of strand transfer and unimolecular and bimolecular disintegration reactions were investigated by using a panel of chemically modified M-MuLV IN proteins. Functional complementation of an HHCC-deleted protein (NΔ105) by an independent HHCC domain (CΔ232) was severely compromised by NEM modification of either subunit. Productive NΔ105 IN-DNA interactions with a disintegration substrate lacking a long terminal repeat 5′-single-stranded tail also required complementation by a functional HHCC domain. Virus encoding the C209A M-MuLV IN mutation exhibited delayed virion production and replication kinetics.